A Randomized Controlled Trial to Investigate Safety and Variability of Egg Excretion After Repeated Controlled Human Hookworm Infection. (10th July 2020) - Hoogerwerf, Marie-Astrid; Koopman, Jan Pieter R; Janse, Jacqueline J; Langenberg, Marijke C C; van Schuijlenburg, Roos; Kruize, Yvonne C M; Brienen, Eric A T; Manurung, Mikhael D; Verbeek-Menken, Petra; van der Beek, Martha T; Westra, Inge M; Meij, Pauline; et al.
Abstract: Background: Controlled human hookworm infections could significantly contribute to the development of a hookworm vaccine. However, current models are hampered by low and unstable egg output, reducing generalizability and increasing sample sizes. This study aims to investigate the safety, tolerability, and egg output of repeated exposure to hookworm larvae. Methods: Twenty-four healthy volunteers were randomized, double-blindly, to 1, 2, or 3 doses of 50 Necator americanus L3 larvae at 2-week intervals. Volunteers were monitored weekly and were treated with albendazole at week 20. Results: There was no association between larval dose and number or severity of adverse events. Geometric mean egg loads stabilized at 697, 1668, and 1914 eggs per gram feces for the 1 × 50L3, 2 × 50L3, and 3 × 50L3 group, respectively. Bayesian statistical modeling showed that egg count variability relative to the mean was reduced with a second infectious dose; however, the third dose did not increase egg load or decrease variability. We therefore suggest 2 × 50L3 as an improved challenge dose. Model-based simulations indicates increased frequency of stool sampling optimizes the power of hypothetical vaccine trials. Conclusions: Repeated infection with hookworm larvae increased egg counts to levels comparable to the field and reduced relative variability in egg output without aggravating adverse events. Clinical Trials Registration: NCT03257072. Abstract : Repeated exposure to infective Necator americanus larvae does not aggravate adverse events and leads to reduced variability in egg excretion. Repeated sampling improves power for drug or vaccine efficacy studies.